2014
DOI: 10.1016/j.ejvs.2013.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Maximum Diameter Measurements of Descending Thoracic Aortic Aneurysms Using Unformatted Planes versus Images Corrected to Aortic Centerline

Abstract: Corrected diameters were smaller than axial diameters, could be measured with higher repeatability, and were subject to less interobserver variability. Using corrected versus axial measurements would have changed management decisions in up to half of the cases in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 24 publications
2
8
0
1
Order By: Relevance
“…Since then, and along with the transition to 3D imaging, the semiautomated centreline method has become routinely available. Multiple previous studies have reported that axial measurements significantly overestimate diameters when compared with centreline methods, especially in more tortuous aortic segments 25 26. Based on these observations, it has been argued that current guidelines are not adapted to the use of centreline measurements and that the surgical threshold should be shifted to smaller TAA sizes 27.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, and along with the transition to 3D imaging, the semiautomated centreline method has become routinely available. Multiple previous studies have reported that axial measurements significantly overestimate diameters when compared with centreline methods, especially in more tortuous aortic segments 25 26. Based on these observations, it has been argued that current guidelines are not adapted to the use of centreline measurements and that the surgical threshold should be shifted to smaller TAA sizes 27.…”
Section: Discussionmentioning
confidence: 99%
“…Five different measurement parameters were selected in this study, which included all measurement parameters in current literature, and all these parameters were automatically obtained on the post-processing software with high repeatability. The measurement of each parameter was made based on a centerline method, which has been verified with higher repeatability than unformatted axial images ( 15 ). Meanwhile, one purpose of this study was to study whether other measurements rather than the traditional maximum aortic diameter have a smaller change rate between the systolic and diastolic phases and could be used as a reference for stent selection at the aortic arch and proximal descending thoracic aorta, which has been seldom reported, especially at level B (no relevant reports have been published).…”
Section: Discussionmentioning
confidence: 99%
“…The syngo.CT Vascular Analysis (Syngo.via, Siemens Healthcare GmbH, Erlangen, Germany) is a commercially available software. A protocol for the measurement of different parameters using the centerline method was established ( 15 ). This protocol was set to ensure measurements during the systolic and diastolic phases.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, diameters can vary slightly depending on trigger time (end-systolic vs. end-diastolic) and edge selection (leading edge-to-leading edge vs. inner edge-inner edge vs. outer edge-outer edge). In general, it is stressed that measurements should be performed perpendicular to the aortic centerline (i.e., on double oblique images), and that measurement location and methodology should be specified in order to provide for accurate follow-up in individuals with an indication for repetitive imaging [1113].
Fig.
…”
Section: Best Current Practice—aortic Diametersmentioning
confidence: 99%